2017
DOI: 10.1039/c6ra26811k
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Pd/SBA-15 catalyst employing surface-bonded vinyl as a reductant and its application in the hydrogenation of nitroarenes

Abstract: Pd/SBA-15 was synthesised through the reduction of PdCl2 by surface bonded vinyl. The catalyst was effective for the hydrogenation of aromatic nitro compounds under mild conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 46 publications
1
20
0
1
Order By: Relevance
“…The chemical shift peaks at 138.3 and 133.9 ppm should be assigned to the vinyl and phenyl, respectively . And the peaks at 127.4 ppm might be ascribed to the partially overlap of peaks arose from vinyl and phenyl . Due to the low content of vinyl in the SiO 2 (4 %), the chemical shift peaks (138.3 ppm) for vinyl displayed a small peak.…”
Section: Figurementioning
confidence: 92%
See 1 more Smart Citation
“…The chemical shift peaks at 138.3 and 133.9 ppm should be assigned to the vinyl and phenyl, respectively . And the peaks at 127.4 ppm might be ascribed to the partially overlap of peaks arose from vinyl and phenyl . Due to the low content of vinyl in the SiO 2 (4 %), the chemical shift peaks (138.3 ppm) for vinyl displayed a small peak.…”
Section: Figurementioning
confidence: 92%
“…The HRTEM images showed interplanar spacing around 0.23 nm which should be ascribed to the (111) plane of metallic Pd. This showed the PdCl 2 was reduced to Pd(0) successfully by the vinyl group which had been demonstrated in the previous reports . The particle size distribution of Pd was recorded by counted at least 200 particles in several TEM images.…”
Section: Figurementioning
confidence: 92%
“…The Pd/MIL‐101(Cr) shown similar small angle XRD patterns to the as‐synthesized MIL‐101(Cr) revealing that the introduction of Pd had no obvious influence on the crystallinity of MIL‐101(Cr). Additionally, the PXRD patterns showed diffraction peaks around 2θ=40°, 46.5° and 68.1° corresponding to the (111), (200) and (220) crystalline planes of Pd (Figure b) . The intensity of the peaks increased as the content of Pd increased from 2.5% to 10%.…”
Section: Resultsmentioning
confidence: 98%
“…The survey scan XPS spectrum of fresh catalysts showed that the surface elements of the catalysts were mainly composed of C, O, Cr and Pd (Figure a). The high resolution spectrum of Pd 3d showed binding energy peaks at 335.7 eV and 341.1 eV which should be attributed to the Pd(0) species according to the previous literatures . This result was agreed with the XRD which showed the diffraction peaks for the crystalline planes of Pd.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure d, the Pd NPs in Pd@BTU‐SBA‐15d was found to be ultra‐small, having an average size ranging from 1.8 to 4 nm. When only SBA‐15 was utilized instead of the BTU‐functionalized SBA‐15 for the deposition of Pd NPs, particle sizes of greater than 5.5 nm in the nanoreator were found . Also, SEM–EDS analysis was performed for the mesoporous materials.…”
Section: Resultsmentioning
confidence: 99%